Integrating Brief Counselling and Adolescents’ Needs - Littrell, John M.; Zinck, Kirk; Nesselhuf, Diane; Yorke, Charles (Canadian Journal of Counselling and Psychotherapy, 2007)
Brief counselling is a powerful tool for working with adolescents. In the past, brief counselling has focused on strategies for problem-solving and goal-setting, while minimizing its connections to the broader developmental frameworks of human needs (i.e., survival, belonging/love, power, freedom, & fun). Consideration of these basic needs assists in counselling adolescents when working in a brief counselling approach that acknowledges the limited time actually available for counsellor/client interactions. Five counselling cases are examined from the integrated perspectives of a brief counselling approach and William Glasser's theory of human needs.